Ekoteologi dalam Perspektif Filsafat Islam: Refleksi Bencana Banjir di Aceh-Sumatera - Fitri Idani; Ismail Fahmi Arrauf Nasution (Al-Widad, 2026)
Ideally, Islamic teachings provide a comprehensive ethical foundation such as the principles of tawhid, amanah, khalifah, and mizan to guide a harmonious relationship between humans and the natural environment. However, in reality, recurring ecological disasters such as the floods in Aceh–Sumatra reveal a significant gap between these theological ideals and actual environmental practices. This study aims to analyze the Aceh–Sumatra flood phenomenon through the lens of ecotheology in Islamic philosophy, examining how religious values can serve as a moral framework for understanding and responding to ecological crises. This research employs a qualitative library-based method using textual–philosophical analysis of Qur’anic ecological verses, works of classical and contemporary Muslim philosophers, and scientific literature on ecology and disaster studies. The findings indicate that ecological disasters arise not only from natural or structural factors but also from a moral crisis rooted in the disrupted human–nature relationship caused by weak internalization of Islamic ethical values. This study highlights the urgency of integrating Islamic environmental ethics into policy-making and disaster mitigation strategies to reinforce ecological balance and foster spiritual awareness within society.